2007
DOI: 10.1099/ijs.0.64857-0
|View full text |Cite
|
Sign up to set email alerts
|

‘Candidatus Magnetoglobus multicellularis’, a multicellular, magnetotactic prokaryote from a hypersaline environment

Abstract: Phylogenetic analysis and phenotypic characterization were used to assign a multicellular magnetotactic prokaryote the name ‘Candidatus Magnetoglobus multicellularis’. ‘Candidatus Magnetoglobus multicellularis' lives in a large hypersaline coastal lagoon from Brazil and has properties that are unique among prokaryotes. It consists of a compact assembly or aggregate of flagellated bacterial cells, highly organized in a sphere, that swim in either helical or straight trajectories. The life cycle of ‘Candidatus M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
136
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 16 publications
3
136
0
3
Order By: Relevance
“…Occasionally, they appeared to lose the ability to control the division process, resulting in huge aggregates of cells with a diameter of about approximately 40 mm. Despite these differences, fluorescence in situ hybridization with probes specific to MMPs (DeLong et al, 1993;Abreu et al, 2007) confirmed that the microorganisms in culture were Ca. M. multicellularis ( Figure 5).…”
Section: Enrichment Culturementioning
confidence: 99%
“…Occasionally, they appeared to lose the ability to control the division process, resulting in huge aggregates of cells with a diameter of about approximately 40 mm. Despite these differences, fluorescence in situ hybridization with probes specific to MMPs (DeLong et al, 1993;Abreu et al, 2007) confirmed that the microorganisms in culture were Ca. M. multicellularis ( Figure 5).…”
Section: Enrichment Culturementioning
confidence: 99%
“…No unicellular bacterium with or without magnetosomes was observed. The purity of the samples was also checked by amplification and sequencing of 16S rRNA genes according to Abreu et al (2007). The only 16S rRNA gene obtained from MTB was that of Ca.…”
Section: Methodsmentioning
confidence: 99%
“…However, some doubt has been raised regarding the true phylogenetic relationship of this organism (Amann et al, 2006) and the recent isolation of two new gammaproteobacterial rod-shaped MTB (Lefèvre et al, 2010b) suggests that the organism described by Simmons et al (2004) biomineralizes magnetite. Confirmed greigite-producing MTB whose 16S rRNA gene has been sequenced include only the multicellular magnetotactic prokaryote Candidatus Magnetoglobus multicellularis and bacteria morphologically similar to it (Abreu et al, 2007;Simmons and Edwards, 2007). This microorganism consists of an assemblage of genetically identical, Gram-negative bacteria that are capable of collectively migrating along magnetic field lines because of the coordinated rotation of flagella that cover each cell on one side.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations